CH4 dry reforming in fluidized-bed plasma reactor enabling enhanced plasma-catalyst coupling. Issue 54 (December 2021) - Chen, Xiaozhong; Sheng, Zunrong; Murata, Sho; Zen, Shungo; Kim, Hyun-Ha; Nozaki, Tomohiro
Graphical abstract: Highlights: Fluidized-bed plasma reactor was newly developed for dry methane reforming (DMR). Catalyst fluidization enhances the plasma coupling to the surface reactions. Generating a large plasma current is more critical than having a higher E/N. Plasma promotes the forward DMR selectively until the equilibrium is established. The reverse reaction of DMR is possible, but not promoted by plasma at all. Abstract: Dry methane reforming (DMR: CH4 + CO2 = 2H2 + 2CO) was studied in a newly developed fluidized-bed dielectric barrier discharge reactor (FB-DBD). DBD-induced synergistic effect as well as discharge behavior were compared with that of packed-bed DBD reactor (PB-DBD). The forward DMR was promoted dramatically when DBD was generated in the fluidized-bed reactor due to an extended surface area of powdered catalysts and their interaction with plasma-generated reactive species. Moreover, enhanced heat and mass transport, as well as longer residence time, in the FB reactor contribute the dramatic enhancement of DMR performance. Reaction promotion in the thermal FB reactor (without DBD) was quite marginal, verifying that extended surface area in the FB reactor is not effective unless the rate-determining step, known as CH bond breaking, is promoted via vibrational excitation by DBD. Moreover, the reverse reaction of DMR was studied in FB-DBD. The reverse DMR was not influenced by DBD at all; the forward DMR is promoted selectively by DBD until the chemical composition reaches the thermal equilibrium.